Durability Performance of Concrete Debris and Bottom Ash as an Alternative Track Ballast Material - Youventharan, Duraisamy; Putra Jaya, Ramadhansyah; Jeevithan, K. M.; Rokiah, Othman; Mohd Arif, Sulaiman; Yaacob, H. (IOP Publishing, 2021)
Concrete debris and bottom ash has been identified as the potential materials to be used in construction industry. This would certainly reduce wastage produced from construction and demolition (C&D) activities and bottom ash from the power plant. However, the concrete debris waste and the bottom ash are been neither tested nor proven to be feasible in the construction of railway track. This paper will discuss the potential usage of concrete debris collected from destruction site and also the bottom ash waste from Coal Energy Power Plant. Currently, neither concrete debris nor bottom ash is used in railway construction. The main objective of this study is to analyse the engineering properties of bottom ash and concrete debris along with the conventional ballast to verify whether the traditional material can be replaced or otherwise. Experiments such as the sieve analysis test, Los Angeles abrasion test, aggregate impact value test and the aggregate crushing value test were conducted to measure the properties. The engineering properties tested in this research are the hardness, toughness and resistance towards impact and crushing of ballast. In terms of gradation, particle size distribution curve was plotted and compared in this research. It was found that the mixture of concrete debris and track ballast in the proportion of 50:50 each has brought some improvement to the properties and tend to behave close to the existing track ballast. The mixture of concrete debris and track ballast also shows that its crushing resistance is better than the existing track ballast. In conclusion, both the waste materials used in this research is highly potential to partially complement traditional material of track ballast.